The Study on Sea Buckthorn (Genus Hippophae L.) Fruit Reveals Cell Division and Cell Expansion to Promote Morphogenesis - Jing Zhao; Zhihua Zhang; Hongdan Zhou; Zengfu Bai; Kun Sun (Plants, 2023)
Due to its unique flavor and high antioxidant content, the sea buckthorn (genus Hippophae L.) fruit is increasingly favored by consumers. Developing from the perianth tube, the sea buckthorn fruit varies greatly among species in both size and shape. However, the cellular regulation mechanism of sea buckthorn fruit morphogenesis remains unclear. This study presents the growth and development patterns, morphological changes, and cytological observations of the fruits of three Hippophae species (H. rhamnoides ssp. sinensis, H. neurocarpa, and H. goniocarpa). The fruits were monitored every 10–30 days after anthesis (DAA) for six periods in their natural population on the eastern margin of the Qinghai-Tibet Plateau in China. The results showed that the fruits of H. rhamnoides ssp. sinensis and H. goniocarpa grew in a sigmoid mode, while H. neurocarpa grew in an exponential mode under the complex regulation of cell division and cell expansion. In addition, cellular observations showed that the mesocarp cells of H. rhamnoides ssp. sinensis and H. goniocarpa were larger in the area with prolonged cell expansion activity, while H. neurocarpa had a higher cell division rate. Elongation and proliferation of the mesocarp cells were found to be essential factors affecting the formation of fruit morphology. Finally, we established a preliminary cellular scenario for fruit morphogenesis in the three species of sea buckthorn. Fruit development could be divided into a cell division phase and a cell expansion phase with an overlap between 10 and 30 DAA. In particular, the two phases in H. neurocarpa showed an additional overlap between 40 and 80 DAA. The description of the sea buckthorn fruit’s transformation and its temporal order may provide a theoretical basis to explore the growth mechanism of fruits and regulate their size through certain cultivation techniques.